Pemberdayaan Masyarakat Berbasis Potensi Lokal Melalui Kampung Kreatif Dan Independen - Mendyeta Wahyu Prasetya; Tjitjik Rahaju (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
The Kediri City Government, in order to realize the Vision and Mission of the Mayor of Kediri, through the Mayor of Kediri Regulation Number 23 of 2020 concerning technical guidelines for implementing the Plus Community Empowerment Program, created the Kampung Keren program. The Kediri City Government wants to trigger the potential of its people to develop various unique and creative things in their area. It is hoped that Kampung Keren can become a forum for people to explore their talents and skills. This is expected to encourage local economic growth and improve community welfare. The aim of this research is to describe how community empowerment is based on local potential through the Kampung Keren Program (Creative and Independent) in Kampung Pecut which collaborates elements of urban tourism and local culture. This research uses a descriptive method with a qualitative approach. Data collection techniques through observation and interviews accompanied by documentation. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. The results of this research show that community empowerment in Kampung Pecut through the Kampung Keren program is working as expected, the community in Kampung Pecut is being helped by the economic turnaround. The Kampung Keren Program in Kampung Pecut has provided benefits for the community and managers, namely increased knowledge and skills of the community thanks to the training provided, then increased income and standard of living for the community thanks to the large number of tourists who visit Kampung Pecut.